Ensayos sobre aplicación de la Teoría del Estado en las algunas culturas del Perú antiguo - Espinoza Coila, Michael (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2023)
Book chapters with investigations of Theory of the State on the cultures of ancient Peru, carried out by teachers and students of the Professional School of Law of the National University of the Altiplano of Puno.